The Service Sector in the Economy in Poland and European Union Countries - Kwiatkowska, Walentyna (Olsztyn Economic Journal, 2015)
The role of the service sector in the economy is increasing in the process of socio-economic development. This tendency has been confirmed and explained by the three-sector theory formulated by A.G.B. Fisher, C. Clark, and J. Fourastie. The main goal of the paper is to show development tendencies in service sectors in Poland and the EU countries and assess them in view of the three-sector theory. The share of the service sector in the total employment and in the total gross value added in the years 2005-2013/2014 will be analysed together with two sub-sectors including market and non-market services. The research shows that the share of the service sector in total employment and total gross value added has been recently increasing in Poland as well as in other EU countries, but there is a gap in this process between Poland and the most developed EU countries. Moreover, in Poland, the role of market services has been recently increasing much faster than the role of non-market services.